Heritage reporting by the Australian public sector: Possibilities from the concepts of new public governance. Issue 2 (31st May 2019) - Woon, Peir Peir; Chatterjee, Bikram; Cordery, Carolyn J.
Abstract : Purpose: The purpose of this paper is to contribute to the future development of heritage reporting in Australia. Public sector reporting of heritage has been a long-standing issue, due to shortcomings in (sector-neutral) for-profit-based financial reporting standards. Australia's sector-neutral approach does not meet public sector users' information needs. The authors develop a heritage reporting model to balance community and other stakeholders' interests and address prior critiques. Design/methodology/approach: The paper reviews heritage reporting requirements in Anglo-Western Countries, and analyses commentaries and research publications. It evaluates the existing reporting requirements in the context of new public management (which focusses on information and efficiency) and new public governance (NPG) (focussing on balancing interests and quality). Findings: The paper proposes an NPG-based heritage reporting model which includes indicators of performance on the five UNESCO (1972) dimensions and operational guidelines issued by UNESCO (2015). These are identification, presentation, protection, conservation and transmission. The proposed model is consistent with the notion of US SFFAS 29 (the standard for Federal entities). Not all heritage must be capitalised and hence attachment of monetary value, but detailed disclosures are necessary. Research limitations/implications: The authors expect the proposed heritage reporting model to better serve users of heritage information compared to the present Australian Accounting Standards Board 116: Property, Plant and Equipment. Originality/value: The authors' proposed model of heritage reporting attempts to answer Carnegie and Wolnizer's (1995, 1999) six questions, addresses decades of concerns raised in previous literature and provides a new perspective to heritage reporting based on NPG that should better serve users' needs.